ANTI-MICROBIAL ACTIVITY AND DIABETIC WOUND HEALING EFFECTS OF PSIDIUM GUAVA AND MELASTOMA MALABATHRICUM LINN LEAVES GEL IN RATS (SPRAGUE DAWLEY) - Tonny Cortis Maigoda; Refdanita Refdanita; Firdaus Firdaus; Anang Wahyudi; Ahmad Rizal; Jumyati Jumyati (Proceeding B-ICON, 2022)
The purpose of this study was to determine the potential of guava and melastoma malabathricum linn leaves mixed gel activity as anti-microbial and wound healing in experimental rats (Sprague dawley). The thick extracts of melastoma malabathricum linn and guava leaves were made in a gel dosage form with a concentration of 4% and 6% and clindamycin as a positive control. This study used experimental laboratory methods, and the population in this study were white male rats and was carried out in the Pharmacology and Pharmaceutical Laboratory, National Institute of Science and Technology. The pharmacological activity was tested in the form of a gel dosage formula, and the rats were made diabetic through an inducing agent, namely alloxan, then the potential of the extract was seen in repairing diabetic wounds in male rats. Melastoma malabathricum Linn and guava Leaves extract gels have an effect in healing diabetic-induced rat wounds using alloxan. This can be seen from the change in the diameter of wound healing. Secondary metabolites of both plant materials are thought to provide anti-microbial activity and stimulate wound healing which helps epithelial cells and tissues so that they regenerate. The chemical content in the extracts of the test preparation has different mechanisms in helping the healing process.